2022
DOI: 10.7759/cureus.29313
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Operative Notes Against Royal College of Surgeons Guidelines in a Tertiary Health Care Surgical Unit in Lahore

Abstract: Operative notes are important documentation made by the surgical team after a surgical procedure. They outline what happened during the surgery and several aspects of post-operative instructions. The aim of this audit was to compare current practices regarding documentation of these operative notes in a tertiary care hospital in Lahore. The standards used were the recommendations made in the good surgical practice guidelines by the Royal College of Surgeons (RCS) of England in 2014.A prospective closed-loop au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
(9 reference statements)
4
9
0
Order By: Relevance
“…When compared to the initial phase, compliance with certain parameters, such as the surgeon's and assistant's names, and details of the operative procedure, reached a full 100%. These findings are consistent with similar studies [ 7 , 15 - 17 ], where compliance rates were also reported at 99%. Additionally, the recording of the surgery date, time, and classification as elective or emergency achieved compliance rates of 100%, 91%, and 100%, respectively [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When compared to the initial phase, compliance with certain parameters, such as the surgeon's and assistant's names, and details of the operative procedure, reached a full 100%. These findings are consistent with similar studies [ 7 , 15 - 17 ], where compliance rates were also reported at 99%. Additionally, the recording of the surgery date, time, and classification as elective or emergency achieved compliance rates of 100%, 91%, and 100%, respectively [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…In modern healthcare, adept record-keeping is imperative, especially when addressing concerns related to medical malpractice [ 3 - 5 ]. These notes not only act as crucial reference tools for healthcare practitioners dealing with patients' surgical histories but also hold potential relevance in legal proceedings [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed the existing literature for further comparison with our findings. A study by Khalid et al (September 19, 2022) [ 7 ] involved a similar issue at a tertiary hospital in Lahore and documented the following results after completing the audit (against the results from our study). Date of procedure: 100% vs. 100% in our study; time of the procedure: 87.5% vs. 6.25%; elective/emergency procedure: 100% vs. 50%; the name of surgeon and assistant: 100% vs. 100%; the name of the operative procedure: 97.9% vs. 100%; type of incision: 95.8% vs. 100%; operative diagnosis: 97.9% vs. 100%; operative findings: 95.8% vs. 100%; complications encountered: 93.8% vs. 90%; any extra procedure performed with reason: 93.8% vs. 75%; details of tissue removed, added, or altered: 93.8% vs. 71.8%; details of closure technique: 95.8% vs. 100%; anticipated blood loss: 95.5% vs. 9.3%; antibiotic prophylaxis: 97.9% vs. 28.1%; DVT prophylaxis: 60.4% vs. NA; detailed postoperative care instructions: 91.7% vs. 100%; and signature: 100% vs. 100%.…”
Section: Discussionsupporting
confidence: 68%
“…Khalid et al employed a similar strategy in their audit of surgical operation notes, covering the same surgical procedures. The implementation of an enhanced proforma format significantly improved overall documentation accuracy, increasing details recorded from 58.6% to 95.3% in the notes [ 6 ]. The findings of this audit, coupled with the evidence presented, highlight the substantial enhancement achievable in patient care through the implementation of straightforward measures.…”
Section: Discussionmentioning
confidence: 99%